(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, the cognitive-methodical system of developing socio-creative competence in future pedagogues and the development of social activity skills and creative competence in future pedagogues in the conditions of reforms are studied. Pedagogical issues of developing socio-creative competence in future pedagogues were also analyzed based on an integrative approach.